Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

(x)=4(x+3)(3x-8) in standard form

Sagot :

Answer:

12x² +3x = 96

Step-by-step explanation:

x = 4(x + 3)( 3x - 8)

x =  (4x + 12) (3x - 8)

x = 4x(3x - 8) + 12(3x - 8)

x = 12x² - 32x + 36x - 96

x = 12x² + (-32x + 36x) - 96

x = 12x² + 4x - 96

0 = 12x² + 4x -x - 96

0 = 12x² + 3x -96

96 = 12x² + 3x  same as 12x² +3x = 96